Are women with preterm labour at risk for negative birth experience? a comparative cross-sectional study from Iran - Zahra Najafi; Mojgan Mirghafourvand; Solmaz Ghanbari-Homaie (BMC, 2023)
Background The unpredictable nature of preterm labour can be a stressful experience for the mother. The occurrence of preterm birth can lead to the failure of the mother's previous expectations regarding the process of labour and birth leading to negative perception towards birth. Methods This descriptive-analytical cross-sectional study was conducted in Tabriz, Iran. We employed convenience sampling to recruit eligible mothers with term birth (314 women) and preterm birth (157 women). Childbirth Experience Questionnaire 2.0, Preterm Birth Experiences and Satisfaction Scale, and Delivery Fear Scale were used to measure the woman's fear of delivery during labour and birth experience. Data were analysed by general linear model. Results The prevalence of negative birth experience in the term and preterm birth groups was 31.8% and 14.3%, respectively. The results of the multivariable general linear model, after the adjustment of demographic and obstetric characteristics, showed that there was no statistically significant difference between the two groups of mothers with term and preterm birth [β (95% CI): -0.06 (-0.22 to 0.09); p = 0.414] in terms of childbirth experience. However, the fear of delivery had a significant relationship with the childbirth experience [-0.02 (-0.03 to -0.01); p < 0.001]. Conclusion There was no statistically significant difference in terms of women's childbirth experience between the mothers with term and preterm births. The fear of delivery during labour was the predictor of childbirth experience. In order to improve women's childbirth experience, interventions should be made to reduce their fear during labour.